STUDENTS’ READING SKILL BY USING PEER ASSISTED LEARNING (PAL) STRATEGY IN THE VIITH GRADE STUDENTS - Nofriansyah; Indrawati Indrawati; Ihda Husnayaini (Journal of English Teaching, Linguistics and Literature, 2020)
This study was aimed to know the implementation of Peer Assisted Learning (PAL) strategy to improve students’ reading skill at seventh grade of SMP N 3 Sungailiat and to find out whether there was or not any significant difference of students’ reading comprehension between students who were taught by using Peer Assisted Learning (PAL) Strategy and those who were taught by using non PAL strategy. Experimental research with quasi-experimental design was used in this research. The population of study were consisted of 236 students, 67 students as the sample purposively. This study also limited into some sub skills of reading, they were vocabulary knowledge, finding topics and understanding main ideas. The result of the test was analyzed by using statistical analysis of Paired sample t-test and Independent sample t-test. The writer used Pearson Correlation and Cronbach Alpha to know the validity and reliability of the test. Based on the result in research findings, second main point were obtained. First, the implementation of PALS was in good and very good category for attendance and attention aspects based on the observation sheet result even though in some meetings were in average category and low category because of the student talked each other, made noise and not interested with some topics during meetings. Second, the students who were taught by using PALS had higher score in the post test than the students who were taught by using non PALS. In this case, the alternative hypothesis was accepted as t-obtained score for experimental group was 4.141, and it was higher than critical value of t-table (2.04). Finally, it could be concluded that there was a significant difference in students’ reading comprehension between the experimental and control group and the strategy of PALS. Therefore, the result of this study is expected to contribute in developing reading students’ comprehension achievement.